Service failure and recovery in the airline industry: Evidence from the TRNC - Azimli, Asil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
The marketing concept is based on the principle of satisfying customers. The ultimate goal of marketing and marketers is to achieve a high level of customer satisfaction and to enhance the relationship with customers. Loyal customers are the most profitable group for companies. Service failures are unwanted defects but they are inevitable. Service failures can happen both during the process of service delivery and as a result of delivery process. Therefore, to avoid dissatisfaction and keep the current customer satisfied, service providers have a second chance which is called ‘service recovery’. It is important for the service provider to employ effective service recovery strategies to alter undesirable consequences of failures (Maxham, 2001). The aim of the study is to investigate the service failure recovery experiences of airline passengers who are flying to or from Turkish Republic of Northern Cyprus Ercan Airport. This research will identify the failure types that passengers experience during their travel and the recovery strategies used by the service firms. The study also explores customer expectations (the expected recovery action) when the recovery had not been attempted. The study also aims to measure whether passengers are satisfied with the recovery strategies used and their behavioral intentions (e.g., WOM intentions and repurchase intentions) after the recovery process. This study shed light on managing customer relations within the airline industry in North Cyprus. Delay of flight, damaged and lost luggage, uncomfortable seats, and food and beverage quality were identified as the most frequent experienced failure types by passengers. Explanation, apology and professional and friendly staff attitude iv were identified as mostly used recovery strategies by airlines. Explanation, offering a better service and apology were identified as the mostly frequently expected recovery strategies. Further, there exist negative relationships among perceived severity of the service failure and satisfaction with the recovery and time taken to resolve a problem and satisfaction with the recovery (i.e. as time taken and perceived severity increase, satisfaction drops). On the other hand, positive relationships were found among satisfaction with the recovery and overall satisfaction, overall satisfaction and repurchase intentions and overall satisfaction and recommending the airlines. Keywords: Service recovery, satisfaction, loyalty, airline industry, North Cyprus.

Pazarlama konsepti müşteri tatmini prensibine dayanmaktadır. Pazarlamanın ve pazarlamacıların en önemli amacı yüksek müşteri tatmini sağlayarak müşterilerle olan ilişkilerini iyileştirerek geliştirmektir. Zira sadık müşteriler şirketlerin en karlı müşteri gruplarıdır. Hizmet aksaklıkları istenmeyen kusurlar olmakla birlikte maalesef hizmetin kaçınılmaz bir parçasıdırlar. Hizmet aksaklıkları hizmetin hazırlama ve sunma sürecinde veya hizmet sunumundan sonra gerçekleşebilir. Müşteri tatminsizliğini önlemek ve mevcut müşteri tatmini sağlamak için hizmet sağlayıcıların ikinci bir şansları daha vardır ki bu ‘hizmet aksaklığı giderme’ olarak bilinir. Hizmet başarısızlıklarının sebep olacağı istenmeyen sonuçları değiştirmek için hizmet sağlayıcıların etkin hizmet aksaklığı giderme stratejilerine sahip olmaları gerekmektedir. Bu çalışmanın amacı Ercan havalimanını kullanarak Kuzey Kıbrıs Türk Cumhuriyeti’ne gelen veya giden havayolları müşterilerinin yaşadıkları hizmet aksaklığı giderme deneyimlerini araştırmaktır. Bu çalışma hava yolları müşterilerinin yaşadığı hizmet aksaklıklarını ve kullanılan hizmet aksaklığı giderme stratejilerini belirleyecektir. Ayrıca eğer hizmet aksaklığı giderilmemişse müşterilerin bu yönde olan beklentilerini araştıracaktır. Bu çalışma ayrıca havayolu müşterilerinin uygulanan hizmet aksaklığı giderme stratejilerine karşı memnuniyetlerini ve hizmet aksaklığı giderildikten sonra müşterilerin davranışsal niyetlerini (sözlü destek veya tekrar satın alma isteklerini) ölçecektir. vi Bu çalışma Kuzey Kıbrıs havayolları sektöründeki müşteri ilişkileri yönetimine ışık tutmuştur. Uçuş gecikmeleri, kayıp ve zarar görmüş bagajlar, rahatsız uçak koltukları ve ucak yiyecek ve içecek kalitesi havayolları müşterileri tarafından en sık yaşanan hizmet aksaklıkları olarak bulunmuştur. Hava yolu şirketleri tarafından en sık kullanılan hizmet aksaklığı giderme stratejileri olarak açıklama, özür dileme ve profesyonel ve arkadaşça davranan çalışan davranışları görülmüştür. Açıklamada bulunma, daha iyi hizmet sunma ve özür dileme ise havayolu müşterilerin beklentileri olarak ortaya cıkmıştır. Ayrıca, hizmet aksaklığı ile hizmet aksaklığının derecesi ve aksaklığı giderme için gereken süre ile hizmet aksaklığı giderildikten sonraki müşteri memnuniyeti arasinda ters ilişki görülmüştür. Bunun yanında, hizmet aksaklığının giderilmesinin yarattığı müşteri memnuniyeti ile genel müşteri memnuniyeti, genel memnuniyet ile tekrardan satın alma istekleri, ve genel memnuniyet ile tavsiyede bulunmak arasında pozitif ilişkiler görülmüştür. Anahtar Kelimeler: Hizmet aksaklığı giderme, memnuniyet, bağlılık, havayolları, Kuzey Kıbrıs.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2013. Supervisor: Assoc. Prof. Dr. Selcan Timur.
Keywords: Business Administration; Marketing Management; Airlines - Management; Service industries - Airline Industry - Marketing - Cyprus (Turkish Republic of Northern Cyprus, 1983-); Service industries - Airline Industry - Management - Cyprus (Turkish Republic of Northern Cyprus, 1983-); Customer services - Management - Airline Industry - Cyprus (Turkish Republic of Northern Cyprus, 1983-); Service Recovery, Satisfaction, Loyalty, Airline Industry, North Cyprus